Alfred Loisy & modern biblical studies - Morrow, Jeffrey L. (Catholic University of America Press, 2019)
Intro -- Contents -- Preface -- Acknowledgments -- Introduction -- 1. Things New and Old: Loisy's Place in the Controversy over Modernism -- 2. The Bible and Its Ancient Near Eastern Milieu in Nineteenth-Century France -- 3. Loisy's Work in the Study of the Ancient Near East and the Old Testament -- 4. Loisy on the Book of Genesis in Light of Mesopotamian Literature -- 5. Back to the Sources: The History of the Source Critical Tradition upon Which Loisy Drew -- 6. Loisy's Engagement with Biblical Scholarship: Fr. Richard Simon as Heroic Symbol -- 7. Loisy's Defense of Historical Biblical Criticism -- Conclusion -- Selected Bibliography -- Index